Structure-based virtual screening and characterization of a novel IL-6 antagonistic compound from synthetic compound database - Wang J; Qiao C; Xiao H; Lin Z; Li Y; Zhang J; Shen B; Fu T; Feng J (Dove Medical Press, 2016)
Jing Wang,1,* Chunxia Qiao,1,* He Xiao,1 Zhou Lin,1 Yan Li,1 Jiyan Zhang,1 Beifen Shen,1 Tinghuan Fu,2 Jiannan Feng1 1Department of Molecular Immunology, Beijing Institute of Basic Medical Sciences, 2First Affiliated Hospital of PLA General Hospital, Beijing, People’s Republic of China *These authors contributed equally to this work Abstract: According to the three-dimensional (3D) complex structure of (hIL-6·hIL-6R·gp 130)2 and the binding orientation of hIL-6, three compounds with high affinity to hIL-6R and bioactivity to block hIL-6 in vitro were screened theoretically from the chemical databases, including 3D-Available Chemicals Directory (ACD) and MDL Drug Data Report (MDDR), by means of the computer-guided virtual screening method. Using distance geometry, molecular modeling and molecular dynamics trajectory analysis methods, the binding mode and binding energy of the three compounds were evaluated theoretically. Enzyme-linked immunosorbent assay analysis demonstrated that all the three compounds could block IL-6 binding to IL-6R specifically. However, only compound 1 could effectively antagonize the function of hIL-6 and inhibit the proliferation of XG-7 cells in a dose-dependent manner, whereas it showed no cytotoxicity to SP2/0 or L929 cells. These data demonstrated that the compound 1 could be a promising candidate of hIL-6 antagonist. Keywords: virtual screening, structural optimization, human interlukin-6, small molecular antagonist, XG-7 cells, apoptosis